Diagrama de desvio fonatório na clínica vocal - Madazio, Glaucya [UNIFESP] (2009)
Purpose: To identify which characteristics discriminates the hoarseness diagram of adult voices that are predominantly adapted, rough, breathy and strained. Method: 196 adult voice samples of the sustained vowel “ae” were analyzed. They were distributed into two groups, 163 with vocal deviation and 33 with healthy voices. Voice samples were submitted to two types of analyses: acoustic and auditory perceptual. The perceptual analyses focused on the identification of the vocal quality predominance – adapted, rough, breathy and strained and also in the degree of deviation, by using a visual analogue scale and its numeric correspondence. The acoustic analyses was performed by means of the VoxMetria software (CTS Informatica) and consisted of assessing the configuration of vocal sample distribution in the hoarseness diagram according to normality area, density, shape and location in the quadrants, and the extraction of fundamental frequency, jitter, shimmer, correlation and GNE. Results: There was a significant difference in the position of the voice samples in relation to the normality area of the diagram, meaning that 100% (33) of the adapted voices were located inside this area and 69.3% (113) of the deviated voices were outside it (p<0.001). Adapted voices presented concentrated density (78.8%, 26), which were statistically different from the deviated voices (56.4%, 92) that presented spread density (56.4%, 92). As far as voice type is concerned, all adapted voices were located at the inferior left quadrant, 45% (27) of the rough voices were at the inferior right, 52.6% (30) of the breathy voices were at the superior right and 54.3% (25) of the strained were at the inferior left. Concerning the degree of severity of vocal deviation, 93.8% of the 16 deviated voices evaluated as having a 1 degree of deviation were located at the inferior and superior right quadrants. In the other hand, 80 % (8) of the voice with a severe degree of deviation were located in the superior right quadrant. The inferior left quadrant concentrated the voices evaluated by the visual analogue scale up to 35.5mm (degree 1) and some from 35.5 to 50.5mm (degree 2). Voices with 3 degree of deviation were located in the inferior right Abstract and both superior left and right quadrants. The voices with the worse degree of deviation were located at the superior right quadrant. Jitter and shimmer differed the strained voices from the rough voices (p<0.021 e p=0.0032 respectively) and from the breathy voices (p=0.021 e p=0.005, respectively). The GNE did also differ the strained voices from the rough voices (p=0.003) and from the breathy voices (p<0.002).It also differentiated the rough from the breathy voices (p<0.001). The correlation between F0 and the other acoustic parameters was not significant and the quality of correlation was very poor: jitter (p=0.257; -8.9%), shimmer (p=0.158; -11.2%), correlation (p=0.285; 8.4%) and GNE (p=0.790; -2.1%). Conclusions: The hoarseness diagram differentiated the adapted from the deviated voices. Adapted voices were located in the normality area, and the majority of the deviated voices were outside it. There was not a relationship between type of voice, density and shape of configuration of vocal sample distribution in the diagram. The distribution of voices in the quadrants related to the type and degree of severity of voice deviation. GNE was the only acoustic parameter able to differ from the three types of deviated voices.